Preference Mapping Selection Of Smartphone’s Brands And Prices Based On Allowance Using Multiple Correspondence Analysis - Husna, Maulida Rahmatul; Astutik, Suci (Proceedings of the International Conference on Green Technology; Vol 8 No 1 (2017): Proceedings of the International Conference on Green TechnologyDO - 10.18860/icgt.v8i1.625, 2017)
The use of smartphone plays an important role for the community and among students, particularly students of the University of Brawijaya Malang where the needs of information increasingly dominate. The needs of the student can be affected by student’s allowance, because the majority of students have additional allowance. The mapping can be done to obtain information about the preferences selection brand smartphone and smartphone based on the price of the allowance. Statistical methods that can be used for mapping is Multiple Correspondence Analysis (MCA). The purpose of this research is to apply for MCA selection preference mapping brand smartphone and smartphone’s price based of the allowance so that the information obtained by the relationship of allowance against the selection preferences of smartphones. The research using primary data with purposive technique sampling that comes from the spread of the questionnaire with respondents was University students of Brawijaya Malang batch 2015. With MCA acquired a two-dimensional graph with the diversity proportion of 76,103%, there are three cluster shaped: obtained the information of students who got high allowance have preference to choose two type of price Rp 2.500.000 – Rp 3.000.000 or mote than Rp 3.000.000 the preference selected brand are Iphone, Samsung or Sony. Medium Allowance range have a preference of price Rp 2.000.000 – Rp 2.500.000, preference of selected brand were Vivo, Lenovo, Oppo or Asus, and low allowance have two type price preference Rp 1.500.000 or Rp 1.500.000 – Rp 2.000.000. LG, Smartfren Microsoft, Xiaomi or Advan are selected preference brand.